SCANNING ELECTRON MICROSCOPIC (SEM), HISTOLOGICAL AND MORPHOLOGICAL STUDY OF THE MONGOOSE (Herpestes ichneumon L., 1758) TONGUE IN SOUTH TURKEY - A. Haligur; S. Ozkadif1; A. Alan; Y. Yener (Journal of Animal and Plant Sciences, 2020)
This study aimed to investigate the scanning electron microscopic (SEM), histological and morphological characteristics of the tongue and papillae in Egyptian mongoose (Herpestes ichneumon L, 1758). The tongues of two (one female, one male) dead mongoose tongue was used as material. The tongues of the mongooses were removed via the dissection method and morphometric measurements were taken. The tongues were fixed in 10% buffered formalin solution. Scanning electron microscopy and histological analyses were performed. According to the results, there were four types of papillae; filiform, fungiform, vallate, and foliate. The filiform papillae differed in terms of type and location on the tongue. It was seen that the filiform papillae had an arrow shape in the lateral cuts. The filiform type was observed on the tip of the tongue, both filiform and bound types on the middle of the tongue and both conic and hook types on the root. The foliate papillae were located laterally in the tongues and did not have ducts. There were four vallate papillae in the tongue of the male mongoose and three vallate papillae in that of the female mongoose. This study presents the first SEM, histological and morphological analyses of the tongue and its papillae in the Egyptian mongoose found in Turkey.
Keywords: Mongoose; papillae; SEM; wild animal